WDR34, a candidate gene for non‐syndromic rod‐cone dystrophy. Issue 2 (9th November 2020) - Solaguren‐Beascoa, Maria; Bujakowska, Kinga M.; Méjécase, Cécile; Emmenegger, Lisa; Orhan, Elise; Neuillé, Marion; Mohand‐Saïd, Saddek; Condroyer, Christel; Lancelot, Marie‐Elise; Michiels, Christelle; Demontant, Vanessa; Antonio, Aline; et al.
Abstract: Rod‐cone dystrophy (RCD), also called retinitis pigmentosa, is characterized by rod followed by cone photoreceptor degeneration, leading to gradual visual loss. Mutations in over 65 genes have been associated with non‐syndromic RCD explaining 60% to 70% of cases, with novel gene defects possibly accounting for the unsolved cases. Homozygosity mapping and whole‐exome sequencing applied to a case of autosomal recessive non‐syndromic RCD from a consanguineous union identified a homozygous variant in WDR34 . Mutations in WDR34 have been previously associated with severe ciliopathy syndromes possibly associated with a retinal dystrophy. This is the first report of a homozygous mutation in WDR34 associated with non‐syndromic RCD. Abstract : Homozygosity mapping and whole‐exome sequencing applied to a case of autosomal recessive non‐syndromic rod‐cone dystrophy (RCD) from a consanguineous union, A, identified a missense homozygous variant in WDR34, c.1241A>G; p.(Asp414Gly)). Mutations in WDR34 have been previously associated with severe ciliopathy syndromes possibly associated with a retinal dystrophy, B. These findings made WDR34 an attractive candidate gene underlying non‐syndromic autosomal recessive RCD. This is the first report of a homozygous mutation in WDR34 associated with non‐syndromic RCD.